Effects of calcinations time on Jc of YBa2Cu307-8 HTSC with nano-CaO addition / Mujaini M … [et al.] - M, Mujaini; S.Y, Yahya; I, Hamadneh; R, Abd. Shukor (2008)
The effects of calcination time on critical current density, Jc of YBa2Cu307-8 superconductor system prepared via co-precipitation method were investigated. In this work, the calcination time was varied for 12 hours and 24 hours. This work also studies on different amount addition of nano-CaO with (YBa2Cu307-8)x (x= O.2wt%-1.Owt%). The results shows that (YBa2Cu307-8)x (x= O.5wt%) at 24 hours calcination time exhibit the best performance of Jc (-5.5864 A/cm2). The results indicate that an introduction of appropriate amount of nano-CaO at optimum time of calcination can effectively improve the flux pinning by performing the best value of Jc .